Determinants of Hotel Operators’ Decisions to Adopt SNI CHSE Certification in Post-Pandemic Indonesia - Oktapianty, Oky Dwi; Eddyono, Fauziah; Sulistyadi, Yohanes (Yayasan Sinergi Kawula Muda, 2025)
The COVID-19 pandemic has had a significant impact on the tourism and hospitality sectors, prompting the need for standardized health and safety protocols to restore public trust. In response, the Indonesian government introduced the SNI CHSE (Cleanliness, Health, Safety, and Environment) certification, which was initially provided free of charge during the pandemic. However, in the post-pandemic period, the certification transitioned into a paid program, creating new challenges for adoption among hotel business operators. This study aims to analyze the influence of certification product, certification cost, and promotion on hotel operators’ decisions to pursue SNI CHSE certification. Employing a quantitative approach through a survey method, data were collected from 100 hotel business actors affiliated with the Indonesian Hotel and Restaurant Association and analyzed using SEM-PLS. The findings reveal that all three factors product, cost, and promotion significantly influence the decision to undertake certification. These results provide strategic implications for policymakers and tourism industry stakeholders in strengthening sustainable tourism recovery through broader CHSE certification implementation, as well as practical implications for designing more effective certification schemes, pricing strategies, and targeted promotional efforts.